A general design procedure for gas–liquid Taylor flow T-junction microreactors. Issue 5 (2nd March 2023) - Chang, Yu; Sheng, Lin; Deng, Jian; Luo, Guangsheng
Abstract : A gas flow rate prediction model under constant pressure operation and a cross-device energy efficiency prediction model are proposed. A Taylor flow T-junction microreactor design procedure is proposed. Abstract : There are many studies on the gas–liquid Taylor flow in T-junction microdevices, but the general design rules for gas–liquid microreactors are not well developed. This work is trying to develop a general design method for gas–liquid Taylor flow T-junction microreactors. Two significant issues must be addressed for the design, which are to determine the relationship between the gas flow rate and the pressure drop in the microreactor, and to know the bubble generation and hydrodynamics of the Taylor flow in different devices. For the first issue, a dimensionless relationship between the gas pressure and the gas flow rate is proposed by determining the pressure drop. For the second issue, a model based on energy efficiency is developed to predict the bubble generation process behavior which can be adapted to different devices. The hydrodynamics in different devices are also investigated. Lastly, a procedure is proposed for the design of gas–liquid Taylor flow T-junction microreactors.